APPLICATION OF NUMBERED HEAD TOGETHER (NHT) TYPE COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING OUTCOMES AND LEARNING ACTIVITIES IN ONE-VARIABLE LINEAR EQUATION AND INEQUALITY MATERIAL FOR GRADE VII STUDENTS - Nindia Ayu Asdaputri; Lumbantobing, Happy; Nainggolan, Jonner (Jurnal Ilmu Pendidikan Indonesia, 2026)
This research is a classroom action research (CAR) conducted in two cycles. This study aims to improve learning outcomes and learning activities of students by implementing the Number Head Together (NHT) type cooperative learning model on the material of linear equations and inequalities of one variable. This research was conducted at SMP Negeri 7 Sentani with the research subjects being 25 class VII B. Data collection techniques were carried out through teacher observation, student observation, and individual tests.. The results show that: 1) The application of the NHT type cooperative learning model can improve learning outcomes in the material on linear equations and inequalities of one variable in class VII B of SMP Negeri 7 Sentani. This is proven by the classical average data of the results of the student learning outcome test which increased by 71% in cycle 1 and 83% in cycle 2. The average value of students also increased by 69 in cycle 1 and 75 in cycle 2. The effectiveness of using this learning model increased with an n-gain of 0.59 in cycle 1 and 0.50 in cycle 2. 2) Student learning activities in learning linear equations and inequalities of one variable increased. In cycle 1, student learning activities increased from 70% in the first to 75% in the second meeting. Classical learning activities in general reached 71%. In addition, in cycle 2, student learning activities also increased from 83% in the first to 88% in the second meeting. Classical learning activities in general reached 88%.